New and rare sponges from the deep shelf of the Alboran Island (Alboran Sea, Western Mediterranean) - Sitjà, Cèlia; Maldonado, Manuel (Zootaxa, 2014)
The sponge fauna from the deep shelf (70 to 200 m) of the Alboran Island (Alboran Sea, Western Mediterranean) was investigated using a combination of ROV surveys and collecting devices in the frame of the EC LIFE+ INDEMARES Grant aimed to designate marine areas of the Nature 2000 Network within Spanish territorial waters. From ROV surveys and 351 examined specimens, a total of 87 sponge species were identified, most belonging in the Class Demospongiae, and one belonging in the Class Hexactinellida. Twenty six (29%) species can be regarded as either taxonomically or faunistically relevant. Three of them were new to science (Axinella alborana nov. sp.; Axinella spatula nov. sp.; Endectyon filiformis nov. sp.) and 4 others were Atlantic species recorded for the first time in the Mediterranean Sea (Jaspis eudermis Lévi & Vacelet, 1958; Hemiasterella elongata Topsent, 1928; Axinella vellerea Topsent, 1904; Gelliodes fayalensis Topsent, 1892). Another outstanding finding was a complete specimen of Rhabdobaris implicata Pulitzer-Finali, 1983, a species only known from its holotype, which had entirely been dissolved for its description. Our second record of the species has allowed a neotype designation and a restitution of the recently abolished genus Rhabdobaris Pulitzer-Finally, 1983, also forcing a slight modification of the diagnosis of the family Bubaridae. Additionally, 12 species were recorded for the first time from the shelf of the Alboran Island, including a few individuals of the large hexactinellid Asconema setubalense Kent, 1877 that provided the second Mediterranean record of this "North Atlantic" hexactinellid. ROV explorations also revealed that sponges are an important component of the deep-shelf benthos, particularly on rocky bottoms, where they make peculiar sponge gardens characterized by a wide diversity of small, erect species forming a dense "undergrowth" among a scatter of large sponges and gorgonians. The great abundance and the taxonomic singularities of the sponge fauna occurring in these deep-shelf bottoms strongly suggest these habitats to be considered within the environmental protection of the Nature 2000 Network.